KRIMINALISASI JURNALIS TERHADAP PUBLIKASI PRODUK JURNALISTIK DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Koswara Koswara; Gialdah Tapiansari Batubara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
The policy of criminalizing journalists due to the publication of journalistic products in the form of reporting in print and electronic media is a setback for press freedom in Indonesia. From January to December 2021, the Press Council surveyed on the Press Freedom Index (IKP) in 34 provinces. As a result, the national IKP score has increased compared to the survey conducted the previous year to 77.88 (quite independent). Even so, there is still criminalization of journalists regarding published reports accused of containing insults or defamation. Existing laws and regulations, the Criminal Code and Law Number 40 of 1999 concerning the Press have not yet regulated the classification of journalistic activity deviations which include criminal acts. The Press Law protects the actions of journalists to carry out their profession including seeking, obtaining, possessing, storing, processing, and conveying information to the public so that these actions cannot be subject to criminal sanctions. The research method used is juridical-normative which is carried out by examining library materials sourced from laws and regulations, books, and journals. The study results show that law enforcers in Indonesia still use criminalization against journalists who carry out their profession.